ANALYSIS OF THE FACTORS AFFECTING DIVIDEND POLICY - Fajar Rina Sejati; Sahrul Ponto; Septyana Prasetianingrum; Sumartono Sumartono; Nona Naomi Sumbari (Universitas Airlangga, 2020)
The purpose of this study was to examine the effect of Free Cash Flow, Debt Policy, Return On Assets, Company Growth on Dividend Policy. The sample of this study was using 10 companies in the Consumer Goods Industry Sector on the Indonesia Stock Exchange (IDX) in 2015-2018 met all the criteria. Empirical evidence suggests that Free Cash Flow has a Significant Effect on Dividend Policy. Debt Policy Has Negative and Significant Impact on Dividend Policy. Whereas Return On Assets and Company Growth Have No Significant Effect on Dividend Policy.